2012
DOI: 10.1055/s-0032-1317181
|View full text |Cite
|
Sign up to set email alerts
|

Chemo- and Regioselective 4CR Synthesis of Oxathiaaza[3.3.3]propellanes via Sequential C–S, C–N and C–O Bond Formation in a Single Pot

Abstract: Oxathiaaza[3.3.3]propellane derivatives were prepared by reaction of in situ generated asymmetric thioureas with intermediate Knoevenagel adducts resulting from ninhydrin and malononitrile. This four-component sequential transformation performed in one reaction flask represents a general route to this unexplored valuable class of sulfur-nitrogen heterocycles. The chemoselectivity and regiochemistry of the products were established by IR, NMR and single crystal X-ray analysis.Multicomponent reactions (MCRs) off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Propellanes as annulated tricyclic systems with a common carbon–carbon covalent bond, have many applications in synthesis of bioactive medicinal compounds 1 or polymers. 2 These tricyclic systems are part of many natural products, such as modhephene 1, 3 canataxa 2 (ref. 4 ) and hasubanan alkaloids 3 (ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Propellanes as annulated tricyclic systems with a common carbon–carbon covalent bond, have many applications in synthesis of bioactive medicinal compounds 1 or polymers. 2 These tricyclic systems are part of many natural products, such as modhephene 1, 3 canataxa 2 (ref. 4 ) and hasubanan alkaloids 3 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, Alizadeh and his co-workers have successfully reported the catalyst free synthesis of the heterocyclic [3.3.3] propellanes by the domino four-component reactions. 3 In 2013 Some of heterocyclic propellanes were prepared using Et 3 N in ethanol by Yan et al 14 Due to the limitations of homogeneous catalysts, heterogeneous catalysts were used to synthesis of propellane indeno indoles. In 2017, these compounds were prepared using CSB-Ni( ii ) as a heterogeneous catalyst 15 and in 2021, the hollow mesoporous boron nitride spheres decorated by CuO was successfully prepared and used as an efficient catalyst for the synthesis of [3.3.3] propellane indeno[1,2- b ] indole derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods are reported for the synthesis of heterocylic [3.3.3]propellanes. Oxa-aza [3.3.3]propellanes were synthesized by Alizadeh et al [4,[22][23][24], Yavari et al [25], Chen et al [26] and Zhang et al [27]. Hassan et al reported the formation of oxaaza-and bisoxathia-aza [3.3.3]-propellanes via nucleophilic addition of symmetrical and unsymmetrical N 1 ,N 2 -disubstituted-1,2-dicarbothioamides on dicyanomethylene-1,3-indanedione 1 [28].…”
Section: Introductionmentioning
confidence: 99%
“…Some other novel synthetic approaches have been established in recent years for the synthesis of tetrahydroimidazo[1,2-a]pyridines by heterocyclic ketene aminals (HKAs). [25][26][27][28][29] Heterocyclic ketene aminals (HKAs) have been proven to be efficient synthons in the synthesis of heterocyclic systems. During the past few years, reactions of cyclic ketene aminals with a variety of biselectrophilic compounds have been applied to make veand six-membered fused heterocycles.…”
Section: Introductionmentioning
confidence: 99%